Предмет: Алгебра,
автор: delesmy
Упростить : 2cos(a- п/3) - 2sin (п/3+ a)
Ответы
Автор ответа:
0
sin (П/6 + а) - sin (a - П/6) =
= 2 * sin {(П/6 + а) + (a - П/6)}/2 * cos {{(П/6 + а) - (a - П/6)}/2 =
= 2 * sin (2a) * cos (2П/6) =
= 2 * sin (2a) * cos П/3 =
= 2 * sin (2a) * 1/2 =
= sin (2a)
= 2 * sin {(П/6 + а) + (a - П/6)}/2 * cos {{(П/6 + а) - (a - П/6)}/2 =
= 2 * sin (2a) * cos (2П/6) =
= 2 * sin (2a) * cos П/3 =
= 2 * sin (2a) * 1/2 =
= sin (2a)
Похожие вопросы
Предмет: Математика,
автор: Ksunia52
Предмет: Английский язык,
автор: Аноним
Предмет: Литература,
автор: zannaminulina2
Предмет: Алгебра,
автор: nodiratashev